Synthesis, Characterisation and Flocculation Properties of Carboxymethyl Cellulose-g Acrylamide (Journal of Sciences, Islamic Republic of Iran)
Graft copolymers of acrylamide on carboxymethyl cellulose (d.s 0.4-0.5) were prepared by the use of ceric ion, ceric ion/reductant molecule initiator systems in aqueous medium. The graft copolymers were characterized by IR spectroscopy. The extent of graft copolymerisation was measured in terms of grafted chains as a function of both ceric ion and ceric ion/reductant molecule concentrations. It was found that introduction of reductant molecule resulted in up to 13 fold increase in percent graft levels. Flocculation of the copolymer samples and ungrafted carboxymethyl cellulose were studied using synthetic effluent of Kaolin (0.25%) in distilled water. The flocculation capacity measured in terms of reduction in the turbidity was found to be highest for carboxymethyl cellulose-g acrylamide and was dependent on the number and molecular size of the grafted polyacrylamide.